Acceptability and understanding of front-of-pack nutritional labels: an experimental study in Mexican consumers - Vargas-Meza, Jorge (BMC Public Health, 2019)
BACKGROUND: Front-of-package labelling is a cost-effective strategy to help consumers make healthier choices and informed food purchases. The effect of labels is mediated by consumer understanding and acceptability of the label. We compared the acceptability and understanding of labels used in Latin-America among low- and middle-income Mexican adults. METHODS: Participants (n = 2105) were randomly assigned to one of three labels: Mexican Guideline Daily Allowances (GDA), Ecuador’s Multiple Traffic Lights (MTL), or Chile’s Warning Labels (WL) in red. Label acceptability was evaluated through items regarding likeability, attractiveness and perceived cognitive workload. Objective understanding was evaluated by asking participants to select the product with the lowest nutritional quality among three products. We measured the time participants took to choose the product. Differences in label acceptability, understanding and time required to choose a product across labels were tested. RESULTS: Compared to the GDA, a higher proportion of participants liked the MTL and WL, considered them attractive, and with a lower perceived cognitive workload (p < 0.05). Participants had 4.00 (2.86–5.59) times the odds of correctly identifying the product with the lowest nutritional quality when using the MTL label and 4.52 (3.24–6.29) times the odds when using the WL, in comparison to the GDA. Time required to choose the product was lower for the MTL (Median: 11.25 s; IQR = 8.00–16.09) and the WL (Median = 11.94 s, IQR = 8.56–16.52) compared to the GDA (Median: 15.31 s; IQR = 10.81–20.21; p < 0.05). No differences were observed between the MTL and the WL. CONCLUSIONS: GDA had the lowest acceptability and understanding among the labels tested. The MTL and the WL were more accepted and understood, and allowed low- and middle-income consumers to make nutrition-quality related decisions more quickly. WL or MTL may foster healthier food choices in the most vulnerable groups in Mexico compared to the current labelling format.